Методи прогнозу речовинного складу та мінеральних фаз вугільних териконів Західного Донбасу - Павличенко А. В.; Младецький І. К.; Дрешпак О. С. (НТУ "ДП", 2024)
Мета. Обґрунтування методики випробування вугільного техногенного родовища. Purpose. Justification of the methodology for testing a coal technogenic deposit.
Methods for predicting the material composition and mineral phases of coal terricones of the Western Donbas
Keywords: техногенні родовища; випробування; кореляційні функція; шахтні відвали; корисні фракції; класи крупності; technogenic deposits; testing; correlation function; mine dumps; useful fractions; size classes